RATE CONSTANTS FOR CHEMICAL-REACTIONS OF RADICALS AT LOW-TEMPERATURES - Clary, D; Stoecklin, T; Wickham, A (1993)
A theoretical analysis is given of the rate constants for the fast reactions of linear molecular radicals in 2Π electronic states with various ionic and molecular partners. Emphasis is given to the temperature dependence of the rate constants in the limit of very low temperature. Significant differences in these temperature dependences are observed for the reactions of 2Π molecules with ions and with neutral 2Π molecules when compared with the analogous reactions for molecules in 1Σ states. Various examples are considered of importance to interstellar chemistry, including the reactions of OH(2Π) and CH(2Π) with H3+, the OH + SO reaction and CH + HD → CD + H2.